BRAND AMBASSADOR SEBAGAI STRATEGI MARKETING TOKOPEDIA MELALUI SELEBRITI KOREA SELATAN TAHUN 2021: (Studi Kasus: Tokopedia dengan Blackpink) - Rizky Annisa Putri; Megahnanda Alidyan Kresnawati (Journal Publicuho, 2023)
Brand ambassador is a part of the marketing strategy which is currently used by several companies to promote or increase sales. Several companies has also collaborated with world leaders who are expected to be able to drive product sales and become the company’s attractiveness to the public. This research aims to describe Tokopedia’s marketing strategy with South Korean celebrity through Blackpink as their brand ambassador in 2021. This research is analyzed using the theory or concept of Celebrity Endorsement and Marketing Mix Strategy. This research is descriptive-qualitative in order to examine as systematic and accurate description of certain facts. The research results showed that with the support of celebrities and implementing a marketing mix strategy, Tokopedia has succeeded in creating sales boost and also has a good corporate image in front of the Indonesian society by involving South Korean celebrities, namely Blackpink as Tokopedia’s brand ambassador in 2021.